PENGARUH PERUBAHAN PTKP TERHADAP JUMLAH WAJIB PAJAK ORANG PRIBADI, PENERIMAAN PAJAK PENGHASILAN DAN KEPATUHAN - Karina, 08.05.52.0061; Wahyudi, Djoko (Students Journal of Accounting and Banking, 2013)
This study aims to determine the effect of the number of individual taxpayers, individual income tax revenues and taxpayer compliance after any changes to the personal exemption for 2008-2009.The data in this study is secondary data. Data obtained from the Tax Office Primary Tegal. With the entire sample population and individual taxpayers in the years 2008-2009 KPP Prtama tegal the individual income tax receipts of article 25, the number of taxpayers and taxpayer compliance. With the analysis used in this study is the difference t-test.These results indicate that the amount of the taxpayer does not significantly influence changes in taxable income, while income tax revenue to section 25 of the Personal and taxpayer compliance significantly influence changes in taxable income.It can be seen from the results of different test t-test. On further research to add variables such as income tax receipts article 21 and add years of recearch.Keywords: The number of taxpayers, Revenue Income Tax Article 25, the Taxpayer Compliance